НЕКЛАССИФИЦИРУЕМАЯ КАРДИОМИОПАТИЯ В РАМКАХ МОНОГЕННЫХ СИНДРОМОВ И ХРОМОСОМНЫХ ЗАБОЛЕВАНИЙ У ДЕТЕЙ - Сдвигова, Наталия Андреевна; Басаргина, Елена Николаевна; Гандаева, Лейла Ахатовна; Деревнина, Юлия Владимировна; Савостьянов, Кирилл Викторович; Журкова, Наталия Вячеславовна (Медицина: теория и практика, 2020)